2016
DOI: 10.1007/s12272-016-0713-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of P2X7/NF-κB pathways by Schisandrin B contributes to attenuation of lipopolysaccharide-induced inflammatory responses in acute lung injury

Abstract: The aim of the present study was to assess the effects and mechanisms of Schisandrin B (SchB) on lipopolysaccharide (LPS)-induced acute lung injury (ALI). ALI was induced in mice by intratracheal instillation of LPS (1 mg/kg), and SchB (25, 50, and 75 mg/kg) was injected 1 h before LPS challenge by gavage. After 12 h, bronchoalveolar lavage fluid (BALF) samples and lung tissues were collected. Histological studies demonstrated that SchB attenuated LPS-induced interstitial edema, hemorrhage, and infiltration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…chinensis , has been reported to exhibit anti-inflammatory properties in inflammatory bowel disease, neuroinflammatory damage, and acute lung injuries. 14 – 16 For the first time, to the best of our knowledge, we report the protective effect of Schisandrin B on cartilage degeneration via suppression of NF-κB and MAPK pathways in this study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…chinensis , has been reported to exhibit anti-inflammatory properties in inflammatory bowel disease, neuroinflammatory damage, and acute lung injuries. 14 – 16 For the first time, to the best of our knowledge, we report the protective effect of Schisandrin B on cartilage degeneration via suppression of NF-κB and MAPK pathways in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Studies focusing on the molecular mechanism revealed that Schisandrin B could effectively reduce the activation of inflammatory signal pathways including nuclear factor-κB (NF-κB) pathway and MAPK/extracellular signal-regulated kinase (Erk)/p38/c-Jun amino-terminal kinase (Jnk) pathway. 10 13 Several in vivo studies have also demonstrated the protective role of Schisandrin B in inflammatory bowel disease, 14 neuroinflammatory damage, 15 acute lung injuries, 16 etc. However, the effect of Schisandrin B on chondrocyte inflammation and OA progression has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…There is compelling evidence from KO experiments and pharmacological interferences that P2X 7 is relevant for the pathogenesis of ARDS [ 98 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 204 , 205 ] ( Figure 2 ). A hallmark of ARDS is excessive invasion and activation of neutrophils (PMN) in the alveolar space.…”
Section: The Role Of P2 Receptors In Lung Diseasementioning
confidence: 99%
“…Extracellular adenosine triphosphate activates P2X 7 R and then the NLRP3 inflammasome, followed by caspase-1 activation, which releases mature interleukin (IL)-1β, thereby promoting inflammation. 13 P2X 7 R is involved in the process of proinflammatory cytokine production, 12,14 the cell cycle, 15 apoptosis, autophagy induction 12,16 and host defenses against infectious pathogens. 17 Additionally, P2X 7 R plays a vital role in immune responses to infections, including sepsis.…”
Section: Introductionmentioning
confidence: 99%